Preparation and Adsorption Performance on Congo Red of Sodium Alginate-Lanthanum Hydrogel Spheres - Dan Dang; Mei Lei; Xinyi Jiang; Rui Song; Gaimeng Yan; Wenju Liu (Advances in Materials Science and Engineering)
Sodium alginate-lanthanum (SA/Lan) hydrogel spheres were prepared by ion cross-linking method to remove Congo Red (CR) in an aqueous solution. The adsorption performance was assessed through batch experiments. The experiment revealed that the highest adsorption capacity of SA/Lan for CR was achieved when the mass concentration of La3+ was 1%, the dosage was 2 g·L−1, the initial concentration of CR was 30 mg·L−1, the adsorption time was 60 min, and the reaction temperature was 25°C. The adsorption capacity of 10.81 mg·g−1 was the corresponding figure. The adsorption process was consistent with the Langmuir and pseudosecond-order models.